PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI POLITEKNIK KESEJAHTERAAN SOSIAL BANDUNG - Adi Suparwo; Muhammad Harli Firmansyah; Rina Dwi Handayani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to determine the influence of the work environment on employee performance at the Bandung Social Welfare Polytechnic, including the lack of harmony in work, employees receiving less positive input, resulting in reduced potential and innovation in employees. The lack of a high social spirit will remind each other, resulting in less warm interactions and harmonious relationships between fellow employees. This research uses descriptive and verification methods taken by researchers in solving a problem. The type of research used in this research is a quantitative method. The population in this study was 40 people so the sample taken was 40. This was taken from the number of active employees at the Bandung Social Welfare Polytechnic Office using a saturated sample formula, which means that the entire population was sampled. The analyzes used in this research include normality tests, simple regression and partial hypothesis testing (t test). Based on the hypothesis testing carried out in this research, the research results show that the work environment greatly influences the performance of Bandung social health polytechnic employees.